Planning The Preparation Of Financial Statements Based On Sak Indonesia For Emkm In The Cake Business (Case Study On Jhonykwe) - Amelia, Siska; Vegirawati, Titin; Dini, Maya (Jurnal Akuntansi, Manajemen dan Bisnis Digital, 2024)
Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM) are prepared as a guideline so that small to medium-scale business actors can more easily prepare financial reports that meet standards. The main objective is to simplify the process of recording and reporting finances for MSMEs. Jhonykwe is one example of a home business engaged in the industrial sector, and this study focuses on how the accounting recording process and the preparation of its financial reports are carried out based on the provisions of SAK EMKM. This study uses a qualitative method with a descriptive approach, where data is collected through interviews, observations, and documentation from primary and secondary sources. Based on findings in the field, financial recording in Jhonykwe is still limited to cash inflow and outflow records and profit and loss reports, and has not fully followed the standards set out in SAK EMKM. This condition is caused by a lack of understanding of the preparation of financial reports and limitations in terms of human resources.